Analisis Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) pada Usaha Mikro di Apotek Manggala Jaya Manado - Langi, Louis Crisitofel; Elim, Inggriani; Latjandu, Lady (Manajemen Bisnis dan Keuangan Korporat, 2025)
Financial accounting standards for micro, small and medium entities (SAK EMKM) are standards specifically for MSMEs. This research aims to analyze how SAK EMKM is implemented in the Manggala Jaya Pharmacy micro-enterprise. The research method used is descriptive qualitative. The results of the research show that Manggala Jaya Pharmacy only makes one financial report, namely a profit and loss report which is not in accordance with SAK EMKM, this is due to the lack of knowledge of human resources at Manggala Jaya Pharmacy regarding accounting science and also understanding of making financial reports in accordance with standards. The results of preparing financial reports in accordance with SAK EMKM are financial position reports, profit and loss reports, and notes to financial reports.